SURVIVAL BENEFITS DOMINATE THE WHOLE LIFE RISK COVERAGE AMONG THE RURAL POPULATION OF RAIPUR POSTAL DIVISION OF CHHATTISGARH STATE - Asha Ramteke, SK Khanuja , OP Chandrakar,Tapesh Gupta (International Journal of Research Science and Management, 2016)
Rural Postal Life Insurance (RPLI) is a measure Insurance sector as well as an approachable savings and investment tool for almost the population of rural India. In present study a comparison is made among the two insurance policies of RPLI within the Postal Circle of Raipur Division namely Whole Life Assurance (Gram Suraksha) which provides the whole life risk coverage in a nominal premium and Endowment Assurance (Gram Santosh) which provide the survival benefit for a stipulated time period and get returns after maturity, and risk coverage get turn off. A statistically significant difference (0.05 % significance level) is found in the selling of both policies within five financial years with the highest selling of Endowment Assurance policy than the Whole Life Assurance. The paid premium for the both policies during five financial years of study is also significantly high (0.001 level) in Endowment policies than the Whole Life Assurance, which seems that the survival benefits dominates the Whole life risk coverage in RPLI.